2016
DOI: 10.7717/peerj.1961
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factors in tomatoes: genome-wide identification, phylogenetic analysis and expression profiling under development and heat stress

Abstract: The HSF (heat shock factor) gene family contains highly conserved plant-specific transcription factors that play an important role in plant high-temperature stress responses. The present study aimed to characterize the HSF transcription factor genes in tomato (Solanum lycopersicum), which is an important vegetable crop worldwide and the model plant for fruit development studies. Twenty-six SlyHSF genes were identified in tomato, and the phylogenetic analysis showed the possible evolution profile of subgroups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…In the current research, the up-regulation of a putative HsfB2b during ripening suggests a role of this TF in regulating pear ripening. This is in agreement with the results in previous research with tomato and Chinese grapevine, in which several members of Hsf family were shown to be involved in fruit ripening [61,62]. Moreover, apple HsfB2a was up-regulated during the late stage of fruit growth, when fruit reached 20 mm in diameter [63].…”
Section: Functions Of Genes Encoding Transcription Factors In the Lt-supporting
confidence: 93%
“…In the current research, the up-regulation of a putative HsfB2b during ripening suggests a role of this TF in regulating pear ripening. This is in agreement with the results in previous research with tomato and Chinese grapevine, in which several members of Hsf family were shown to be involved in fruit ripening [61,62]. Moreover, apple HsfB2a was up-regulated during the late stage of fruit growth, when fruit reached 20 mm in diameter [63].…”
Section: Functions Of Genes Encoding Transcription Factors In the Lt-supporting
confidence: 93%
“…Several HSFs have been cloned from different species since the yeast HSF was first isolated in the 1980s (Baniwal et al, 2004;Bharti et al, 2004;Czarnecka-Verner et al, 2004;Kotak et al, 2004;Zhu et al, 2006;Guo et al, 2008;Yang et al, 2016). The first plant HSF was cloned from tomato in 1990 (Yokotani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the genome wide identification and characterization of heat shock transcription factor in solanaceous crops, the total lists of HSTs were listed in Table 4. By and large, Hsps has dual functions in both stress and non-stress conditions, which plainly indicates the role it has on the stress response and physiological response by regulating complex regulatory processes which was checked by the gene expression pattern to evaluate its function and tolerance to stresses [117][118][119][120][121][122][123].…”
Section: Heat Shock Transcription Factormentioning
confidence: 99%
“…The genome wide analyses of each transcription factor have been completed and "-"indicates the genome wide analysis was not done yet. Potato's WRKY [63] Dof [58], NAC [145]; ARF [192]; ERF [181] Pepper WRKY [193] ERF [194]; Dof [51] MYB [103]; ARF [190]; NAC [195] Tomato WRKY [62] Dof [53] MYB [88] HSF [120] ARF [196] ERF [171]; Eggplant's WRKY [197] Dof [52] MYB [84].…”
Section: List Of Major Transcription Factors In Major Solanaceous Foomentioning
confidence: 99%